L'Avventura - Nowell-Smith, Geoffrey (Palgrave Macmillan, 2013)
"Michelangelo Antonioni's starkly beautiful L'avventura is one of the great masterpieces of European art cinema, though at Cannes in 1960 it baffled and enraged its first audience. The plot is simple: a woman disappears while visiting a tiny, remote island with friends and it's as if they don't notice that she's gone. What has happened to her? L'avventura disclaims the conventions of narrative cinema in the most radical way: it never provides an answer to this question. Antonioni has often been labelled pessimist but, as Geoffrey Nowell-Smith argues, his work is not judgemental and is better described as sceptical, concerned with truth rather than consolation. L'avventura seems indifferent to either progress or decadence, Nowell-Smith writes: its characters are placed fairly and squarely where they are, with no past to return to or future to advance to. Stripped of consoling certainties, existentially alone, they are observed with a meticulousness that takes nothing for granted. As well as detailing the circumstances of production, Nowell-Smith relates L'avventura to other groundbreaking films of the period and to all of Antonioni's earlier and later work. In order to appreciate the significance of L'avventura, he concludes, it is necessary to understand not only that the film is a classic but also that it was a revolution in cinema."--Publisher description.
"First published in 1997 by the British Film Institute."-- Title page verso.
Keywords: Avventura (Motion picture); L'Avventura (Motion picture); L'avventura (Antonioni)